2015
DOI: 10.1016/j.aca.2015.02.062
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of benzene, toluene, ethylbenzene and o-xylene in internal combustion engine exhaust with time-weighted average solid phase microextraction and gas chromatography mass spectrometry

Abstract: A new and simple method for benzene, toluene, ethylbenzene and o-xylene (BTEX) quantification in vehicle exhaust was developed based on diffusion-controlled extraction onto a retracted solid-phase microextraction (SPME) fiber coating. The rationale was to develop a method based on existing and proven SPME technology that is feasible for field adaptation in developing countries. Passive sampling with SPME fiber retracted into the needle extracted nearly two orders of magnitude less mass (n) compared with expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…It was shown that the TWA model based on Ficks' law works reasonably well for BTEX when the contribution of extraction by metallic parts of the SPME assembly is accounted for [30]. This contribution is reproducible and dependent on the type of compound [30].…”
Section: Objectivesmentioning
confidence: 83%
See 4 more Smart Citations
“…It was shown that the TWA model based on Ficks' law works reasonably well for BTEX when the contribution of extraction by metallic parts of the SPME assembly is accounted for [30]. This contribution is reproducible and dependent on the type of compound [30].…”
Section: Objectivesmentioning
confidence: 83%
“…In our previous research, Woolcock et al [37,38], Baimatova et al [30], and Koziel et al [29] addressed these concerns by proposing to use retracted SPME sampling for benzene, toluene, ethylbenzene and o-xylene (BTEX) in hot gas streams from syngas plant, vehicle exhaust, and phenolics, mercaptans and a heterocyclic amine in potentially infectious process reactor air. Baimatova et al [30] and Koziel et al [39] showed that the adsorption to metallic surfaces of SPME assembly is significant, reproducible, yet can be controlled and accounted for. Adsorption to metallic SPME assemblies is likely more of a concern for PAHs but was not assessed before.…”
Section: Spme For Sampling Of Vehicle Exhaust Gasesmentioning
confidence: 99%
See 3 more Smart Citations